La réforme orthodoxe Église, État et société en Grèce à l'époque de la confessionnalisation post-ottomane (1833-1940) - Anastassiadis, Anastassios (Bibliothèque des Écoles françaises d'Athènes et de Rome (BEFAR), 2020)
The Orthodox Reform is the first comprehensive sociohistorical account of the century-long process of the conservative renovation of the Greek orthodox church, a process that saw the passage to a "modern" religion, religious innovation and social activism come to rime with intolerance on both the religious and political fields. Based on extensive research in public and religious archives of Greece, France and the Vatican as well as an impressive array of pamphlets and periodicals published all around the Eastern Mediterranean, it paints an unprecedented picture of what can be called the Greek-orthodox component of late ottoman confessionalization. Challenging the narratives of an uninterrupted link between an immutable orthodox Church entrenched in tradition and a Greek national state practising religious intolerance ever since its foundation, it argues that the current religious-political configuration in Greece is the product of the major transformations occurring during the Interwar when the zeal of orthodox activists from Greece and the Ottoman empire took advantage of the unparalleled social and national crisis following the 1922 Katastrophi to finally impulse what can be justly called the orthodox version of Reform and usher in a Greek-orthodox modernity.